THE INFLUENCE OF ENTREPRENEURIAL CULTURE IN INDONESIA TOWARDS BUSINESS STUDENTS’ INTENTION TO BE AN ENTREPRENEUR - Agus Deva Adhikusuma; Genoveva Genoveva (FIRM Journal of Management Studies, 2020)
Human capital in Indonesia is still lack of entrepreneur which is only 3.31% became an entrepreneur in 2018, this is still lower from World Bank standard that a country should have more than 4% entrepreneur from the total population within a country. This study aims to find out the influence between education, family background, subjective norm, and perceived behavioral control towards entrepreneurial intention to faculty of business students in the Jabodetabek area. The primary data in this study was gathered by distributing 186 survey questionnaires for faculty of business students in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) areas. This research used survey method through questionnaires, such as assumption analysis and multiple regression. The result showed Subjective Norm has no significant influence on entrepreneurial intention. Education, Family Background, and Perceived Behavioral Control have significant influences toward Entrepreneurial Intention. This research also found that all independent variables simultaneously influence on Entrepreneurial Intention. Adjusted R square is 0.460, it means that 46% changes independent variable (Entrepreneurial Intention) is influenced by independent variables such as education, family background, subjective norm, and perceived behavioral control. This is recommended for business students in Indonesia especially the Jabodetabek area should more confidence with their capabilities and have a positive mindset to become entrepreneurs.